Pengaruh Media Crossword Puzzle Terhadap Hasil Belajar Siswa Pada Materi Operasi Hitung Perkalian Bilangan Cacah - Nurwahyunita, Nina; Wulan, Budhi Rahayu Sri; Nurhayati, Eni (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
The motivation of this research is to know the influence of crossword puzzle media on student learning outcomes on operating material and student response to learning using crossword Puzzle media in class IV at SDN Masangan Wetan. Quantitative methodology was used in this exploration with a Pre-Experimental Design type of research using a Nonequivalent Control Group Design research design. The data collection techniques used in this research are validation by material experts and media, learning outcomes, pretest and posttest, students response questionnaires. The result from the hypothesis is using a simple linear test ( t test). Based on the description of the calculating results of the student response questionnaire, an overall score was 81.2%. The results of the t-test hypothesis test show that t-count 5.655 > t-table 2.100 and 0.00 < 0.05 means  is dismissed. Based on the results of the research, the conclusion was that there was an influence of the use of crossword puzzle media on student learning outcomes as well as the presence of excellent student response to learning using crossword media puzzle in class IV.